Analysis and evaluation of the pull‐out behavior of hooked steel fibers embedded in high and ultra‐high performance concrete for calibration of numerical models. (18th June 2019) - Gebuhr, Gregor; Pise, Mangesh; Sarhil, Mohammad; Anders, Steffen; Brands, Dominik; Schröder, Jörg
Abstract: This paper aims at extending the existing knowledge regarding the pull‐out behavior of single steel fibers embedded in high‐ and ultra‐high‐strength concretes with compressive strengths exceeding 100 MPa. Apart from the compressive strength, straight fibers, and fibers with hooked‐ends as well as different embedded lengths are considered. The experiments have shown that the bond strength for straight fibers increases with an increasing compressive strength, mechanical anchorage in terms of hooks multiply the load‐bearing capacity. For hooked end fibers in ultra‐high performance concrete (UHPC) fiber rupture occurred. Special attention was paid to characterize scatter adequately. Especially for hooked‐end fibers in UHPC conventional slip‐wise averaging does not represent the maximum load well. Therefore, a more precise approach basing on characteristic points is introduced. The experimental results are presented to be used for calibration and validation of numerical models. As an example, an elasto‐plastic phase‐field model using a Drucker‐Prager yield condition is developed, which represents the pull‐out behavior of straight fibers satisfyingly.